3cosx-1=cosx

Simple and best practice solution for 3cosx-1=cosx equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3cosx-1=cosx equation:


Simplifying
3cosx + -1 = cosx

Reorder the terms:
-1 + 3cosx = cosx

Solving
-1 + 3cosx = cosx

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-1cosx' to each side of the equation.
-1 + 3cosx + -1cosx = cosx + -1cosx

Combine like terms: 3cosx + -1cosx = 2cosx
-1 + 2cosx = cosx + -1cosx

Combine like terms: cosx + -1cosx = 0
-1 + 2cosx = 0

Add '1' to each side of the equation.
-1 + 1 + 2cosx = 0 + 1

Combine like terms: -1 + 1 = 0
0 + 2cosx = 0 + 1
2cosx = 0 + 1

Combine like terms: 0 + 1 = 1
2cosx = 1

Divide each side by '2osx'.
c = 0.5o-1s-1x-1

Simplifying
c = 0.5o-1s-1x-1

See similar equations:

| 9(z+2)-2z=-17 | | -15=.50(x+6) | | 7w+5-3+-2w=4w-6+w+8 | | 2x-3+x-10=20 | | 2x-3x+532= | | 43=n-6 | | 4ln(x)-8=0 | | 83=m-10+14-1-7 | | 8w+5z=x+3 | | 9a-5=2a+5 | | 0=16t^2-48t+64 | | 9.8*.06= | | -0.25y+4=1 | | 58+z=87 | | X=8x+17 | | (2x-4)(3x+8)=0 | | 238=14t | | -2x+12=x-4+x | | W+11=100 | | -16t^2-18t+210=0 | | (X-6)(y+8)=0 | | 4=80-q | | f(x)=-0.06x^3+18x^2+800x-5000 | | 4y^2=50 | | -5+4y=53 | | -1=4(w-4)-7w | | 2x+6-5x=14-14x+11x-8 | | 4m^3-21m-18=0 | | 3+4(2-x)=3x+(-x-7) | | 19z=95 | | X^2+10w-2=0 | | 0.12(18)+0.002X=0.06(12+X) |

Equations solver categories